1998
DOI: 10.1042/bj3320695
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of a vacuolar-type H+-ATPase in the plasma membrane and intracellular vacuoles of Trypanosoma cruzi

Abstract: Acid-loaded Trypanosoma cruzi amastigotes and trypomastigotes regained normal cytoplasmic pH (pHi), as measured in cells loaded with 2',7'-bis-(2-carboxyethyl)-5(6)-carboxyfluorescein (BCECF), by a process that was sensitive to bafilomycin A1 at concentrations comparable to those that inhibited vacuolar (V) H+-ATPases from different sources. Steady-state pHi was also decreased by similar concentrations of bafilomycin A1 in a concentration-dependent manner. The efflux of H+ equivalents from amastigotes and tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 65 publications
(85 reference statements)
0
26
1
1
Order By: Relevance
“…V-PPase may contribute to parasitic cytosolic pHstasis by pumping H + into the acidocalcisomes [17,23]. However this organelle accumulates also Ca and other divalent cations such as Zn and Fe which co-precipitates with large amounts of polyphosphates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…V-PPase may contribute to parasitic cytosolic pHstasis by pumping H + into the acidocalcisomes [17,23]. However this organelle accumulates also Ca and other divalent cations such as Zn and Fe which co-precipitates with large amounts of polyphosphates.…”
Section: Discussionmentioning
confidence: 99%
“…However this organelle accumulates also Ca and other divalent cations such as Zn and Fe which co-precipitates with large amounts of polyphosphates. For this reason, they have been suggested to participate in several cellular processes such as osmoregulation [37], storage of high-energy polyphosphate for mobilization in case of stress or great energy demands [47,48], in pHstasis [23] and the Ca 2+ homeostasis [25,49]. We have previously shown that the endoplasmic reticulum of Herpetomonas sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imunocytochemical quantification using DAMP as a probe showed that reservosomes have a luminal pH of about 6.0 (Soares et al 1992). However, it is still a matter of speculation how these organelles are acidified, as they were not labeled with antibodies against a vacuolar-type H + -ATPase, which however recognized other intracellular vacuoles, possibly the acidocalcisomes (Benchimol et al 1998). A 52-kDa protein sharing sequence homology with glutathione S-transferase (Tc52) has been also localized in reservosomes (Ouassi et al 1995).…”
Section: The Endocytic Pathwaymentioning
confidence: 99%